Electro-adsorption method for efficiently and circularly removing perfluorinated compounds in water and electrode material
By using nano-Fe3O4/chitosan/activated carbon composite electrode for electrosorption, the problems of low removal efficiency of perfluoro compound and easy electrode material falling off in the prior art are solved, and efficient and circulating perfluoro compound removal is achieved, which is characterized by green environmental protection and low energy consumption.
Patent Information
- Application Number
- CN202411868809.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The prior art is not efficient when removing low-concentration perfluoro compounds in water, and the electrode material is prone to fall off, has a small adsorption capacity, and is not easy to desorption, making it difficult to achieve rapid and efficient removal.
The nano-Fe3O4/chitosan/activated carbon composite electrode is used as the anode and the activated carbon is used as the cathode. The operating voltage of 0.8 to 5V is applied for electrosorption, and the adsorption capacity and desorption efficiency are improved by modifying the electrode material.
It has achieved efficient adsorption and desorption of perfluoro compounds. The electrode materials are reusable, green, safe and environmentally friendly, and can recover perfluoro compounds, reducing energy consumption and pollution.
Smart Images

Figure HDA0005195222900000011 
Figure HDA0005195222900000012 
Figure HDA0005195222900000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water pollutant treatment, and specifically relates to an efficient and cyclic electric adsorption method and electrode material for removing perfluorinated compounds in water. Background Art
[0002] Perfluorinated compounds are compounds formed when all hydrogen atoms on the carbon chain of a molecule are replaced by fluorine atoms. They are difficult to degrade and will accumulate in the environment and the human body. Perfluorinated compounds have been detected at certain concentrations in most important water bodies in China, such as the Yangtze River and the Yellow River. Perfluorinated compounds are also widely found in fire extinguishers, clothing coatings, and paints in daily life. The Centers for Disease Control and Prevention of the United States evaluated blood samples from more than 16,000 people between 1999 and 2016 and found that per- and polyfluoroalkyl substances (PFAS) were detected in the blood of almost all of the subjects. China is also facing serious PFAS pollution. Detection of PFAS in six water plants in central and eastern China found that perfluorooctanoic acid (PFOA) and perfluorohexanoic acid (PFHxA) were the main PFAS in drinking water. A certain concentration of PFOA was still detected in the treated drinking water, ranging from 0.38 to 51.0 ng·L -1 between.
[0003] Technologies such as photochemical oxidation, ultraviolet irradiation, electrochemical oxidation, ultrasonic irradiation, adsorption, coagulation, and zero-valent iron reduction have been developed for the removal of PFSA from aqueous solutions. However, these methods are not effective and economical enough for the removal of low concentrations of PFSA. It is still urgent to develop an effective technology for the removal of PFSA under low energy consumption and mild experimental conditions.
[0004] Capacitive deionization (CDI, also known as electrosorption) has the advantages of good adsorption selectivity, low energy consumption, easy recycling, no secondary pollution and low operating cost. It has good application prospects, attracting the attention of many scholars and becoming one of the current research hotspots. The most critical part of CDI technology is the selection and modification of electrode materials. The selected electrode materials mainly need to have high specific surface area, good hydrophilicity, suitable pore size distribution, high conductivity and other characteristics.
[0005] At present, there are few studies on the application of CDI in the field of perfluorinated compound removal, and the current research mainly focuses on reducing the common ion effect in the electrosorption process by adding ion exchange membranes, thereby increasing the adsorption capacity of electrosorbed perfluorinated anions.<Separation and Purification Technology> A research result published by (348(2024)127728) introduces the effectiveness of the ACDI system with only CEV (cation exchange membrane) added to remove short-chain PFAS (PFBS) from aqueous solution. The traditional CDI configuration does not contain an ion exchange membrane between the electrodes, which consists of only two 100μm nylon spacers. The MCDI device includes a cation exchange membrane (CMV, SelemionTM, AGC Engineering Co., Japan) behind the negative electrode and an anion exchange membrane (AMV, SelemionTM, AGC Engineering Co., Japan) near the positive electrode. The ACDI in this study modified the design of MCDI and omitted the anion exchange membrane. The results showed that the deionization capacity of the CDI system with the addition of anion exchange membrane was 28.75mg / g, which is 2.7 times and 3.3 times that of CDI and MCDI (membrane CDI), respectively.
[0006] Directly modifying carbon materials as electrode materials is a more convenient application solution for CDI systems. By modifying activated carbon, the affinity for the target adsorbed ions is enhanced, thereby reducing the common ion adsorption effect. Compared with CDI systems with ion exchange membranes, CDI systems with directly modified activated carbon as electrode materials are easier to assemble and more convenient to apply. In addition, membraneless CDI devices are more environmentally friendly and have no risk of secondary pollution.
[0007] At present, the main problems of CDI technology for removing perfluorinated compounds with carbon electrodes are: the electrode material is easy to fall off, the adsorption capacity is small, and it is not easy to desorb. Therefore, it is of great significance to introduce new carbon composite materials with high efficiency and easy desorption to quickly remove perfluorinated compounds. Summary of the invention
[0008] In view of the above problems, the present invention takes perfluorobutane sulfonic acid, the most widely distributed perfluoro compound, as the target, and invents a method and electrode material for removing perfluoro compounds from water based on nano-Fe3O4 / chitosan / activated carbon composite electrode capacitive deionization, which can effectively adsorb perfluorobutane sulfonic acid in water. After desorption, the electrode material retains high-efficiency adsorption capacity. The electrode material has the characteristics of repeated use, green, safe and environmentally friendly, and perfluoro compounds can be recycled.
[0009] The technical solution adopted by the present invention is as follows:
[0010] An efficient and cyclic electrosorption method for removing perfluorinated compounds from water, characterized in that a nano-Fe3O4 / chitosan / activated carbon composite electrode is used as an anode, activated carbon is used as a cathode, a working voltage of 0.8 to 5V is applied, and the electrosorption is performed in a water body;
[0011] The nano-Fe3O4 / chitosan / activated carbon composite electrode is prepared by the following method:
[0012] (1) adding chitosan to an acetic acid solution to fully dissolve it, then adding nano-ferroferric oxide and mixing it thoroughly, and then adding activated carbon and a cross-linking agent to obtain a slurry;
[0013] (2) completely drying the slurry obtained in step (1) to obtain a block of carbon sheets, and grinding the block to obtain a powder;
[0014] (3) The powder obtained in step (2) is mixed with a binder solution to fully dissolve to obtain a composite electrode slurry, which is then evenly coated on a titanium plate to obtain a nano-Fe3O4 / chitosan / activated carbon composite electrode.
[0015] Preferably, in step (1), the mass ratio of chitosan to nano-ferroferric oxide is (0.8-1.2):1, and the mass ratio of chitosan to activated carbon is 1:(5-35).
[0016] Preferably, in step (1), the concentration of the acetic acid solution is 1% to 3%, the added mass of chitosan is 0.2% to 2% of the volume of the acetic acid solution, and the added amount of the cross-linking agent is 1 to 3 vol%.
[0017] Preferably, step (1) is specifically as follows: adding chitosan to the acetic acid solution, ultrasonicating at 20-50°C for 20-40 minutes, placing in a 20-40°C water bath and stirring for 20-40 minutes to fully dissolve, then adding nano-iron tetroxide, stirring and mixing in a 60-90°C water bath for 1-3 hours, then adding activated carbon and continuing to stir for 1-2 hours, then adding a cross-linking agent, and stirring at 60-90°C for 5-8 hours.
[0018] Preferably, in step (1), the cross-linking agent is at least one of methyltrimethoxysilane and glutaraldehyde; and the mass ratio of chitosan to activated carbon is 1:(14-18).
[0019] Preferably, the drying temperature in step (2) is 50-100° C., and the drying time is 15-24 hours; the powder is ground into powder and sieved to a mesh size of 40-200.
[0020] Preferably, in step (3), in the binder solution, the binder is at least one of propylene oxide and polyvinylidene fluoride, and the solvent is at least one of ethanol and dimethylacetamide.
[0021] Preferably, in step (3), the mass ratio of the binder to the powder obtained in step (2) is 1:(8-10); the mass ratio of the binder to the solvent is 1:(30-50).
[0022] Preferably, the operating voltage is 0.8-1.6V.
[0023] An electrode material is a nano-Fe3O4 / chitosan / activated carbon composite electrode used in the method of the present invention.
[0024] The present invention uses chitosan as the raw material for modified activated carbon, because it will be positively charged after protonation, which can enhance the adsorption of anions by the anode. After the activated carbon is modified by chitosan, the hydrophilicity of the electrode becomes stronger, the surface properties are improved, and more adsorption sites are added, so that its adsorption capacity is improved. In addition, the hydroxyl and amino functional groups rich in chitosan can form hydrogen bonds with the sulfonic acid functional groups in perfluorosulfonic acid, thereby enhancing the selective adsorption ability of the electrode. Another modified raw material is magnetic nano-iron tetroxide, which has high electrical conductivity, which can be attributed to the electrons in Fe 2+ with Fe 3+ It can be used as an anode material for supercapacitors and lithium-ion batteries, showing good electrochemical properties. Therefore, the modification of chitosan with magnetic Fe3O4 can effectively improve the electrochemical properties of chitosan on carbon-based electrode materials. The magnetic chitosan obtained by modifying chitosan with nanomagnetism has a stronger positive charge after protonation, and is more likely to adsorb negatively charged anions during electrical adsorption. There are cation-π interactions between the two bonds of Fe=O and S=O in ferroferric oxide, which can be beneficial to the selective adsorption of perfluorosulfonic acid anion groups.
[0025] Compared with the prior art, the advantages of the present invention are as follows:
[0026] 1. The present invention adopts the CDI method of new carbon electrode materials to efficiently adsorb and desorb perfluorinated compounds, recycle the carbon electrode materials, enrich and concentrate perfluorinated compounds, and has the characteristics of being green and environmentally friendly, safe and controllable, low in energy consumption, recycled, and basically emission-free.
[0027] 2. The magnetic ferroferric oxide selected in the present invention has high electrical conductivity, which can be attributed to the electrons in Fe 2+ with Fe 3 + It can be used as an anode material for supercapacitors and lithium-ion batteries, showing good electrochemical properties, and thus can effectively improve the electrochemical properties of electrode materials.
[0028] 3. After the present invention uses chitosan to modify the activated carbon, the hydrophilicity of the electrode becomes stronger, and water can more fully infiltrate the electrode surface, further improving the performance and efficiency of electrical adsorption.
[0029] 4. Chitosan and nano-Fe3O4 are positively charged. The present invention uses chitosan and nano-Fe3O4 to modify the activated carbon, which makes the positive charge of the anode stronger and adsorbs perfluorinated compounds as much as possible, which can effectively reduce the common ion adsorption effect. Compared with the CDI system of the traditional unmodified carbon electrode system, the adsorption capacity is increased.
[0030] 5. The hydroxyl and amino functional groups rich in the activated carbon composite electrode of the present invention can form hydrogen bonds with the sulfonic acid functional groups in perfluorosulfonic acid, and the Fe=O bond and S=O also have a π-π conjugation effect, which further enhances the adsorption affinity of the electrode for perfluorosulfonic acid.
[0031] 6. Compared with the CDI system with ion exchange membrane, the CDI system with directly modified activated carbon as electrode material is easier to assemble and use, and does not require regular replacement of ion exchange membrane, thus avoiding the risk of group leakage on the exchange membrane and reducing costs.
[0032] 7. The present invention can be coated on different current collectors as required to prepare flat, tubular and rolled membrane components, which is convenient for industrial production and large-scale application.
[0033] 8. The present invention can facilitate the removal and enrichment of perfluorinated compounds by controlling the voltage of 0-5 volts according to the specific perfluorinated compound pollution situation, thereby facilitating the optimization of the removal process. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 It is a comparison chart of the adsorption capacity effect of the embodiment and the comparative example.
[0035] Figure 2 It is a comparison chart of the adsorption capacity of the embodiment and the comparative example changing with time.
[0036] Figure 3 This is a graph of the adsorption capacity of Example 1 within 10 cycles.
[0037] Figure 4 This is a comparison chart of the adsorption capacity of Example 1 at different operating voltages. DETAILED DESCRIPTION
[0038] The technical solutions in the embodiments of the present invention are described clearly and completely below, and the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, other embodiments obtained by ordinary technicians in the field without creative work are all within the protection scope of the present invention.
[0039] The nano-ferroferric oxide used in the examples of the present invention was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; the activated carbon was purchased from Japan Kuraray Co., Ltd., model number YP-50F.
[0040] Example 1
[0041] A method for removing perfluorobutane sulfonic acid from water based on nano-Fe3O4 / chitosan / activated carbon composite electrode capacitive deionization, using nano-Fe3O4 / chitosan / activated carbon composite electrode as anode and activated carbon as cathode to achieve electrical adsorption of perfluorobutane sulfonic acid in water. The following is the preparation process of the anode electrode material:
[0042] (1) Add 0.5 g of chitosan to 100 ml of 2% acetic acid solution, perform ultrasonic treatment at 30°C for half an hour, and then stir in a 30°C water bath for half an hour to fully dissolve. Then take 0.5 g of nano-ferroferric tetroxide and add it to the chitosan acetic acid solution. Stir and mix in a 80°C water bath for 2 hours. Then add 8 g of activated carbon and continue stirring for 1 hour. Then add 2.5 ml of glutaraldehyde and heat and stir at 80°C for 6 hours.
[0043] (2) Pour the slurry obtained in (1) into a flat container, place it in an oven, adjust the temperature to 80°C, and bake it for 18 hours. After it is completely dried, grind the obtained block carbon sheet into a powder that passes through a 100-mesh sieve for use.
[0044] (3) 0.05 g of PVDF was added to 2 g of DMAC and stirred thoroughly to dissolve. Then 0.45 g of the powder in step (2) was added to the PVDF DMAC solution and mixed thoroughly. The mixture was evenly coated on a titanium plate to form the anode of the CDI device, which was recorded as Fe3O4 / CS10.
[0045] Example 2
[0046] A method for removing perfluorobutanesulfonic acid from water based on nano-Fe3O4 / chitosan / activated carbon composite electrode capacitive deionization. 4 / Chitosan / activated carbon composite electrode is used as anode and activated carbon is used as cathode to realize the electrosorption of perfluorobutanesulfonic acid in water. The following is the preparation process of anode electrode material:
[0047] (1) Add 1 g of chitosan to 100 ml of 2% acetic acid solution, perform ultrasonic treatment at 30°C for half an hour, and then stir in a 30°C water bath for half an hour to fully dissolve. Then take 1 g of nano-ferroferric tetroxide and add it to the chitosan acetic acid solution. Stir and mix in a 80°C water bath for 2 hours. Then add 7 g of activated carbon and continue stirring for 1 hour. Then add 2.5 ml of glutaraldehyde and heat and stir at 80°C for 6 hours.
[0048] (2) Pour the slurry obtained in (1) into a flat container, place it in an oven, adjust the temperature to 80°C, and bake for 18 hours. After it is completely dried, grind the obtained block carbon sheet into a powder that passes through a 100-mesh sieve for use.
[0049] (3) 0.05 g of PVDF was added to 2 g of DMAC and stirred thoroughly to dissolve. Then 0.45 g of the powder in step (2) was added to the PVDF DMAC solution and mixed thoroughly. The mixture was evenly coated on a titanium plate to form the anode of the CDI device, which was recorded as Fe3O4 / CS20.
[0050] Example 3
[0051] A method for removing perfluorobutane sulfonic acid from water based on nano-Fe3O4 / chitosan / activated carbon composite electrode capacitive deionization, using nano-Fe3O4 / chitosan / activated carbon composite electrode as anode and activated carbon as cathode to achieve electrical adsorption of perfluorobutane sulfonic acid in water. The following is the preparation process of the anode electrode material:
[0052] (1) 0.25 g of chitosan was added to 100 ml of 2% acetic acid solution, and ultrasonicated at 30°C for half an hour. Then, the mixture was placed in a 30°C water bath and stirred for half an hour to fully dissolve. Then, 0.25 g of nano-ferroferric tetroxide was added to the chitosan acetic acid solution, and the mixture was stirred in an 80°C water bath for 2 hours. Then, 8.5 g of activated carbon was added and stirring was continued for 1 hour. Then, 2.5 ml of glutaraldehyde was added and heated and stirred at 80°C for 6 hours.
[0053] (2) Pour the slurry obtained in (1) into a flat container, place it in an oven, adjust the temperature to 80°C, and bake for 18 hours. After it is completely dried, grind the obtained block carbon sheet into a powder that passes through a 100-mesh sieve for use.
[0054] (3) 0.05 g of PVDF was added to 2 g of DMAC and stirred thoroughly to dissolve. Then 0.45 g of the powder in step (2) was added to the PVDF DMAC solution and mixed thoroughly. The mixture was evenly coated on a titanium plate to form the anode of the CDI device, which was recorded as Fe3O4 / CS5.
[0055] Comparative Example 1
[0056] The difference from the embodiment is that both the anode and cathode of the CDI device use unmodified activated carbon as electrode materials, and the preparation method is as follows:
[0057] 0.05 g of PVDF was added to 2 g of DMAC and stirred thoroughly to dissolve. Then 0.45 g of activated carbon powder was added to the PVDF DMAC solution and mixed thoroughly. The mixture was evenly coated on a titanium plate to form the anode of the CDI device, which was denoted as AC.
[0058] Comparative Example 2
[0059] The difference from the embodiment is that,
[0060] The anode of the CDI device uses only chitosan-modified activated carbon as the electrode material, and the preparation method is as follows:
[0061] (1) Add 1 g of chitosan to 100 ml of 2% acetic acid solution, perform ultrasonic treatment at 30°C for half an hour, and then stir in a 30°C water bath for half an hour to fully dissolve. Then add 8 g of activated carbon and continue stirring for 1 hour. Then add 2.5 ml of glutaraldehyde and heat and stir at 80°C for 6 hours.
[0062] (2) Pour the slurry obtained in (1) into a flat container, place it in an oven, adjust the temperature to 80°C, and bake it for 18 hours. After it is completely dried, remove it and grind the resulting block carbon sheet into a powder that passes through a 100-mesh sieve for later use.
[0063] (3) 0.05 g of PVDF was added to 2 g of DMAC and stirred thoroughly to dissolve. Then 0.45 g of the powder in step (2) was added to the PVDF DMAC solution and mixed thoroughly. The mixture was evenly coated on a titanium plate to form the anode of the CDI device, which was recorded as CS10.
[0064] Application Experiment Example 1
[0065] 1. The performance of Examples 1 to 3 in the field of removing perfluorinated compounds is investigated. The specific results and processes are as follows:
[0066] The composite electrodes of Examples 1 to 3 and Comparative Examples 1 and 2 were used as anodes, unmodified activated carbon was used as cathodes, and the electrode size was 5×5 cm. A voltage of 1.2 V was applied between the anode and the cathode to form an assembly for electro-adsorption of perfluorobutanesulfonic acid. 500 mg / L perfluorobutanesulfonic acid was used as adsorption influent. The perfluorobutanesulfonic acid solution was adjusted to pH 6.5 with 0.1 mol / L sodium hydroxide solution. The treatment volume was 100 mL. Adsorption was performed in a 150 mL beaker. Power was turned on for 15 minutes to complete the capacitive removal of perfluorobutanesulfonic acid. Data of capacitive adsorption of perfluorobutanesulfonic acid were obtained.
[0067] like Figure 1 , 2 As shown, after 15 minutes of power on, the adsorption capacities of Fe3O4 / CS5, Fe3O4 / CS10, and Fe3O4 / CS20 were calculated to be 21.32 mg / g, 30.24 mg / g, and 25.62 mg / g. The adsorption capacity of the unmodified activated carbon as the anode in Comparative Example 1 was 6.21 mg / g, and the adsorption capacity of the chitosan-modified activated carbon as the anode in Comparative Example 2 was 19.68 mg / g. It can be seen that when the modification ratio of nano-Fe3O4 and chitosan is appropriate, the adsorption capacity of perfluorobutane sulfonic acid is significantly improved.
[0068] 2. The recycling process of the nano-Fe3O4 / chitosan / activated carbon composite electrode of Example 1 was investigated: after the capacitor adsorbed PFBS, the adsorbed PFBS was automatically desorbed back into the water after the voltage was disconnected. Figure 3 As shown in the figure, after multiple cycles of adsorption and desorption, the Fe3O4 / CS10 electrode still has a high adsorption capacity.
[0069] 3. The performance of the nano-Fe3O4 / chitosan / activated carbon composite electrode of Example 1 in the field of adsorption of perfluorobutanesulfonic acid was investigated. The specific process and results are as follows:
[0070] 500 mg / L perfluorobutane sulfonic acid was used as the adsorption influent, the pH of the perfluorobutane sulfonic acid solution was adjusted to 6.5 with 0.1 mol / L sodium hydroxide solution, and the treatment volume was 100 mL.
[0071] Effect of operating voltage on adsorption of perfluorobutanesulfonic acid:
[0072] Voltages of 0.8V, 1.2V, and 1.6V were applied between the anode and cathode to electro-adsorb PFBS. The capacitive removal of PFBS was completed after 15 minutes of power-on. Data on capacitive adsorption of PFBS at different voltages were obtained. Figure 4As shown, the calculated adsorption capacity at voltages of 0.8V, 1.2V, and 1.6V is 20.69mg / g, 30.24mg / g, and 38.89mg / g. With the increase of voltage, the electrosorption capacity of the CDI system gradually increases. However, when the voltage is greater than 1.23V, the ions in the water will gain or lose enough electrons, thereby undergoing a chemical reaction to generate hydrogen and oxygen, resulting in electrolysis of water, which is not conducive to its application in the field of water treatment in actual production.
Claims
1. An efficient and recyclable electrosorption method for removing perfluorinated compounds from water, characterized in that: With nano-Fe3O4 / chitosan / activated carbon composite electrode as anode and activated carbon as cathode, a working voltage of 0.8-5V was applied and placed in water for electrosorption; The nano-Fe3O4 / chitosan / activated carbon composite electrode is prepared by the following method: (1) adding chitosan to an acetic acid solution to fully dissolve it, then adding nano-ferroferric oxide and mixing it thoroughly, and then adding activated carbon and a cross-linking agent to obtain a slurry; (2) completely drying the slurry obtained in step (1) to obtain a block of carbon sheets, and grinding the block to obtain a powder; (3) The powder obtained in step (2) is mixed with a binder solution to fully dissolve to obtain a composite electrode slurry, which is then evenly coated on a titanium plate to obtain a nano-Fe3O4 / chitosan / activated carbon composite electrode.
2. According to claim 1, a highly efficient and recyclable electrosorption method for removing perfluorinated compounds from water is characterized in that: In step (1), the mass ratio of chitosan to nano-ferroferric oxide is (0.8-1.2):1, and the mass ratio of chitosan to activated carbon is 1:(5-35).
3. According to claim 2, a highly efficient and recyclable electrosorption method for removing perfluorinated compounds from water is characterized in that: In step (1), the concentration of the acetic acid solution is 1% to 3%, the added mass of chitosan is 0.2% to 2% of the volume of the acetic acid solution, and the added amount of the cross-linking agent is 1 to 3 vol%.
4. According to claim 3, a highly efficient and recyclable electrosorption method for removing perfluorinated compounds from water is characterized in that: Step (1) is specifically as follows: adding chitosan to the acetic acid solution, ultrasonicating at 20-50° C. for 20-40 minutes, placing in a 20-40° C. water bath and stirring for 20-40 minutes to fully dissolve, then adding nano-iron tetroxide, stirring and mixing in a 60-90° C. water bath for 1-3 hours, then adding activated carbon and continuing to stir for 1-2 hours, then adding a cross-linking agent, and stirring at 60-90° C. for 5-8 hours.
5. A highly efficient and cyclic electrosorption method for removing perfluorinated compounds from water according to claim 4, characterized in that: In step (1), the cross-linking agent is at least one of methyltrimethoxysilane and glutaraldehyde; and the mass ratio of chitosan to activated carbon is 1:(14-18).
6. The highly efficient and recyclable electrosorption method for removing perfluorinated compounds from water according to claim 1, characterized in that: The drying temperature in step (2) is 50-100° C. and the drying time is 15-24 hours; the powder is ground into powder and sieved to a mesh size of 40-200.
7. The highly efficient and recyclable electrosorption method for removing perfluorinated compounds from water according to claim 1, characterized in that: In step (3), in the binder solution, the binder is at least one of propylene oxide and polyvinylidene fluoride, and the solvent is at least one of ethanol and dimethylacetamide.
8. A highly efficient and cyclic electrosorption method for removing perfluorinated compounds from water according to claim 7, characterized in that: In step (3), the mass ratio of the binder to the powder obtained in step (2) is 1:(8-10); the mass ratio of the binder to the solvent is 1:(30-50).
9. A highly efficient and cyclic electrosorption method for removing perfluorinated compounds from water according to any one of claims 1 to 8, characterized in that: The working voltage is 0.8-1.6V.
10. An electrode material, characterized in that: The nano-Fe3O4 / chitosan / activated carbon composite electrode is used in the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Textile wastewater treatment method based on Fe3O4 / CNTs composite dispersed electrode
CN112079416A
Enhanced magnetic adsorbent
CN112169773A
Electrochemical biosensor electrode modified composite material and preparation and application thereof
CN118225858A
Electrical doping of iron with chitosan nanoemulsion
US11980937B1
Electrochemical detection of beta-lactoglobulin
US8834704B1
Cited By
Device and method for treating cadmium ions in wastewater through electrochemical adsorption
CN121063656A